EVALUATION OF ALTERNATIVE RAILWAY CONNECTION ACCESS AT JAKARTA SOEKARNO HATTA INTERNATIONAL AIRPORT - Ayu Aprilischa; Imam Muthohar; Richard Moxon (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2015)
Traveling between the center of Jakarta and Soekarno Hatta International Airport (SHIA) is further constrained by the limited number of main routes available which likely cannot be accommodated in the future by road based transport modes alone. Hence, the airport needs to develop airport surface access to accommodate its network. The aim of this research is to analyze the railway access system for developing the system of SHIA using multi criteria analysis in the selection of alternative route alignment of the railway line and a qualitative study in data collection within the research design. Development of the criteria includes technical, economic, environmental and spatial aspect. Three alternatives have been proposed in this analysis, i.e. through West Jakarta, through North and West Jakarta and through North and Central Jakarta. The results show that alternative 3 (through North and Central Jakarta) can give implications to the airport users, i.e. providing a high standard of the rail link in a well-timed manner and a cost-effective public transport link. Improving the multi-modal access to the airport will improve the supply of employment to business, lead to urban regeneration around station locations, and improve Greater Jakarta Metropolitan Area regional competitiveness.